Analisis Kebisingan Dan Getaran Mekanis Pada Mesin Saccof Harvester (Studi Kasus Di Kebun Tebu Cimahpar, Bogor, Jawa Barat) - Sunu Ariastin Kurniawati; Mad Yamin (PERTETA, 2013)
AbstractDevelopment in agricultural mechanization is characterized by the increasing use of agricultural machinery and equipments. It can be seen from sugarcane harvesting process which machinery is used instead of manual equipment. In term of using the harvesting machinery operated by human, the principle of ergonomic should be applied to fulfill the goal of work productivity and ensure occupational health and safety. It is because, during its operation, there will be a potential hazard, caused by noise and vibration, to workers and the environment. This research was aimed to analyze the noise and vibration level of Saccof Harvester during its employment. It was expected that the time limit for the optimal use of the machine can be determined based on the available standard. Furthermore, the method to reduce the negative impacts of noise and vibration can also be identified. According to the research, it was revealed that the noise and vibration level which was received by operator exceeded the ambient level. Consequently, there is necessity to control of noise and vibration on both the source (harvesting machinery) and the receiver (operator). Keywords: Saccof harvester machine, noise, mechanical vibrationAbstrak Perkembangan mekanisasi pertanian dapat dilihat dari peningkatan kebutuhan akan alat-alat mekanik untuk meningkatkan dan mempermudah hasil produksi pertanian. Misalnya adalah dalam proses pemanenan tebu secara mekanis menggunakan mesin pemanen tebu, seperti sugarcane harvester sebagai peralihan dari pemanenan tebu secara manual menggunakan golok atau sabit. Suatu pekerjaan yang dilakukan oleh manusia haruslah menerapkan ergonomi dalam upaya menciptakan kenyamanan, kesehatan, keselamatan, dan produktivitas yang optimal. Penelitian ini bertujuan untuk menganalisa tingkat kebisingan dan getaran mekanis pada mesin pemanen tebu serta mengetahui sebaran tingkat kebisingan yang ditimbulkannya. Semakin tinggi tingkat kecepatan putar motor maka semakin tinggi tingkat kebisingannya dan semakin jauh jarak dari mesin maka tingkat kebisingan akan semakin berkurang. Pengendalian terhadap kebisingan dan getaran serta faktor lain yang dapat meningkatkan keselamatan kerja, dapat dilakukan dengan berbagai cara: pengendalian pada sumbernya atau pengendalian pada penerima atau operator. Kata Kunci: alat pemanen tebu, analisa kebisingan dan getaran mekanik. Diterima: 19 Oktober 2012; Disetujui: 21 Februari 2013